Pathological Correlation of a Cardiac Mass with Multimodality Imaging - Sumit Sohal; Farida A. Tanko; Esad Vucic; Sergio Waxman; Suresh Gupta; Billie Fyfe-Kirschner (Case Reports in Medicine)
Cardiac masses are rarely encountered in clinical practice and can lead to severe hemodynamic consequences. In addition to clinical cues, noninvasive modalities can play an important role in characterization of these masses and therefore their diagnosis and management planning. Here in this case report, we describe the use of various forms of noninvasive imaging techniques to narrow the differential diagnosis and form an operative plan for a cardiac mass later identified as a benign myxoma originating from the right ventricle on histological examination.